Chemical Constituents in Hybrids of Ligularia tongolensis and L. cymbulifera: Chemical Introgression in L. tongolensis. Issue 7 (23rd June 2016) - Shimizu, Anna; Hanai, Ryo; Okamoto, Yasuko; Tori, Motoo; Yu, Jiao‐Jun; Gong, Xun; Kuroda, Chiaki
Abstract : Two samples with morphologies intermediate between Ligularia tongolensis and L. cymbulifera were collected in Desha, Sichuan Province, and one, in Pachahai, Yunnan Province, P. R. China. The DNA sequencing confirmed that the samples were hybrids of the two species. Tetradymol (1 ), the major compound of L. cymbulifera not found in L. tongolensis, was isolated from the hybrid samples collected at both locations, while furanoeremophilan‐15‐oic acid derivative4, a compound characteristic to L. tongolensis, was found in the Pachahai hybrid but not in the Desha hybrids. Thus, the chemical consequence of hybridization can be variable. In addition, analysis of L. tongolensis samples at Pachahai indicated that introgression has been a mechanism of generating chemical diversity in the plant. Eleven compounds including three new ones were isolated. Abstract :